Lignin-based chemical crosslinking polyvinyl alcohol composite membrane and preparation method thereof

Through the esterification modification of succinic anhydride and lignin and the crosslinking of polyvinyl alcohol, a lignin-based chemical crosslinked polyvinyl alcohol composite film with a three-dimensional network structure is formed, and the lignin/polyvinyl alcohol composite film in the prior art is solved. The problem of poor mechanical properties in high humidity environments has achieved good rebound and degradability, and is suitable for high humidity environments.

CN119286016AActive Publication Date: 2025-01-10QILU UNIVERSITY OF TECHNOLOGY (SHANDONG ACADEMY OF SCIENCES)
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411531337.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-01-10
Estimated Expiration
2044-10-30

AI Technical Summary

Technical Problem

The existing lignin/polyvinyl alcohol composite films have poor mechanical properties in high humidity environments, making it difficult to meet good degradability and resilience at the same time, and commonly used crosslinking agents have environmental pollution and toxicity problems.

Method used

Succinic anhydride and lignin are used for esterification modification, and esterification and crosslinking with polyvinyl alcohol to form a crosslinking network with a three-dimensional spatial structure. The lignin-based chemical crosslinked polyvinyl alcohol composite film is prepared by solution casting method. .

Benefits of technology

Maintain good elongation and resilience in high humidity environments, is suitable for high humidity environments, and has good degradability and environmental protection performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119286016A_ABST
    Figure CN119286016A_ABST
Patent Text Reader

Abstract

The invention discloses a lignin-based chemical crosslinking polyvinyl alcohol composite membrane and a preparation method thereof, and belongs to the technical field of high polymer materials. The preparation method provided by the invention comprises the following steps: dissolving lignin and succinic anhydride in a solvent, and reacting in the presence of a catalyst to obtain a succinic anhydride esterified lignin solution; and adding polyvinyl alcohol into the succinic anhydride esterified lignin solution, reacting, and drying to form a film. The preparation method is simple, low in cost and suitable for large-scale preparation; the obtained lignin-based chemically-crosslinked polyvinyl alcohol composite film can still keep the elongation at break of 200% or above in a high-humidity environment with the RH of 90%, has good rebound resilience after being soaked, has the rebound rate of 90% or above and even as high as 100%, is suitable for a working environment which is in a high-humidity environment for a long time and has a high strain requirement on materials, and has good degradation performance at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to a lignin-based chemically cross-linked polyvinyl alcohol composite film and a preparation method thereof. Background Art

[0002] The information disclosed in the background of the invention is only intended to enhance the understanding of the overall background of the invention and should not be necessarily regarded as an acknowledgment or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] Industrial lignin mainly comes from the pulp and papermaking process as a by-product. It is considered to be one of the potential sources of biomass energy and can be converted into fuel and other chemicals. However, the current pulp and paper industry system's main use of lignin is still at a low-value stage. Lignin is either directly discharged into nature for natural degradation or simply collected and burned to provide calorific value for industrial production, resulting in environmental pollution and waste of resources.

[0004] Lignin / polyvinyl alcohol composite film is one of the ways to effectively utilize lignin, and both lignin and polyvinyl alcohol are naturally degradable substances, so it has a broad application prospect in film materials. The current lignin / polyvinyl alcohol composite film is mainly based on physical blending film, but the compatibility between lignin and polyvinyl alcohol is poor, and the obtained blending film has poor mechanical properties. Using a cross-linking agent to cross-link lignin and polyvinyl alcohol to prepare a film material is one of the important ways to improve the mechanical properties of the film. Epichlorohydrin, formaldehyde and glutaraldehyde are the most widely used cross-linking agents at present. However, epichlorohydrin causes slow natural degradation due to the presence of epoxy groups, and formaldehyde itself is highly toxic. If released into the environment in large quantities, it may have a negative impact on the ecosystem; Glutaraldehyde is greatly affected by the environmental pH, and extreme pH may even cause the hydrolysis reaction of glutaraldehyde, affecting the cross-linking performance. In addition, the lignin / polyvinyl alcohol composite film prepared by the above cross-linking agent may be destroyed in a high humidity environment, and the resilience is poor or even does not have resilience. It is difficult to simultaneously meet good degradability and good resilience in a high humidity environment, and the practical value is poor.

[0005] Therefore, it is an urgent problem to provide a lignin / polyvinyl alcohol composite film with good degradability and the ability to maintain good resilience in a high humidity environment. Summary of the invention

[0006] In view of this, the present invention provides a lignin-based chemically cross-linked polyvinyl alcohol composite film and a preparation method thereof. The lignin-based chemically cross-linked polyvinyl alcohol composite film of the present invention has good performance in a high humidity environment, and the elongation at break can still be maintained at more than 200%. It also has good resilience and degradability, and is suitable for working environments that are in high humidity for a long time and have high strain requirements on materials.

[0007] In a first aspect, the present invention provides a method for preparing a lignin-based chemically cross-linked polyvinyl alcohol composite film, comprising the following steps:

[0008] Dissolving lignin and succinic anhydride in a solvent, and reacting in the presence of a catalyst to obtain a succinic anhydride esterified lignin solution;

[0009] Polyvinyl alcohol is added into the succinic anhydride esterified lignin solution, and the solution is dried to form a film after the reaction.

[0010] Preferably, the mass fraction of the lignin is 30-50% of the total mass of lignin, succinic anhydride and polyvinyl alcohol.

[0011] Furthermore, the mass ratio of succinic anhydride to polyvinyl alcohol is 1:(0.8-1.2).

[0012] Preferably, the total mass ratio of lignin, succinic anhydride and polyvinyl alcohol to the solvent is 1 g: (2.5-5) mL.

[0013] Preferably, the solvent is selected from one or more of dimethyl sulfoxide, N,N-dimethylformamide or N,N-dimethylacetamide.

[0014] Preferably, the catalyst is selected from N,N-dimethylbenzylamine 、 Acetone or 1-methylimidazole.

[0015] Preferably, the mass fraction of the catalyst is 15-25% of the mass of succinic anhydride.

[0016] Preferably, in the step of obtaining a succinic anhydride esterified lignin solution by reacting in the presence of a catalyst, the reaction temperature is 55 to 70° C. and the reaction time is 5 to 10 hours.

[0017] Preferably, in the step of drying and film formation after the reaction, the reaction temperature is 55 to 70° C. and the reaction time is 5 to 10 hours.

[0018] Preferably, in the step of drying to form a film after the reaction, the drying is vacuum drying, the drying temperature is 55 to 70° C., and the drying time is 8 to 24 hours.

[0019] In a second aspect, the present invention provides a lignin-based chemically cross-linked polyvinyl alcohol composite film prepared by the above preparation method.

[0020] Compared with the prior art, the present invention has achieved the following beneficial effects:

[0021] (1) The present invention uses succinic anhydride to esterify lignin, and then esterifies and crosslinks it with polyvinyl alcohol through carboxyl groups to form a crosslinked network with a three-dimensional spatial structure. Finally, a lignin-based chemically crosslinked polyvinyl alcohol composite film is prepared by a solution casting method. The preparation method of the present invention is simple, low in cost, and suitable for large-scale preparation;

[0022] (2) The lignin-based chemically cross-linked polyvinyl alcohol composite film prepared by the present invention forms a cross-linked network of polyvinyl alcohol-succinic anhydride-lignin, and the moisture resistance of the material is significantly improved. In a high humidity environment of 90% RH, the elongation at break can still be maintained at more than 200%. Moreover, due to the formation of a good cross-linked skeleton network, it has good resilience after immersion, with a rebound rate of more than 90%, or even as high as 100%, which expands the use environment of the polyvinyl alcohol film and is suitable for working environments that are in high humidity for a long time and have high strain requirements on the material;

[0023] (3) The lignin-based chemically cross-linked polyvinyl alcohol composite film prepared by the present invention has good degradability, becomes brittle and wrinkled after landfill treatment, and has good environmental performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] The drawings constituting part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their description are used to explain the present invention and do not constitute an improper limitation of the present invention. Obviously, for those skilled in the art, other drawings can be obtained based on these drawings without creative work.

[0025] Figure 1 It is a picture of the rebound performance test process of the composite film samples of Examples 1 to 3 of the present invention and Comparative Example 1 in a dry state;

[0026] Figure 2 It is a picture of the resilience performance test process of the composite film samples of Examples 1 to 3 of the present invention after immersion.

[0027] Figure 3 This is a picture of the degradation performance test process of the composite membrane sample of Example 3 of the present invention during natural landfill, wherein a is the initial sample; b is the sample after the first cycle, c is the sample after the second cycle, and d is the sample after the third cycle. DETAILED DESCRIPTION

[0028] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0029] The present invention provides a method for preparing a lignin-based chemically cross-linked polyvinyl alcohol composite film, comprising the following steps:

[0030] Dissolving lignin and succinic anhydride in a solvent, and reacting in the presence of a catalyst to obtain a succinic anhydride esterified lignin solution;

[0031] Polyvinyl alcohol is added into the succinic anhydride esterified lignin solution, and the solution is dried to form a film after the reaction.

[0032] In the present invention, the huge three-dimensional network structure of lignin provides a large number of reaction sites for esterification reaction. Under the action of a catalyst, lignin undergoes esterification reaction with succinic anhydride, and then undergoes esterification reaction with the hydroxyl group of polyvinyl alcohol, forming a cross-linked network with a three-dimensional spatial structure. Relying on the large steric hindrance and rich functional groups of lignin, water molecules are difficult to diffuse inside the material. At the same time, the hydrophilic functional groups of lignin compete with the hydroxyl groups of polyvinyl alcohol to form hydrogen bonds with water. The esterification reaction also consumes part of the hydroxyl groups of polyvinyl alcohol. The three methods effectively prevent the combination of water molecules with the hydroxyl groups of polyvinyl alcohol, reducing the influence of hydroxyl groups on polyvinyl alcohol. Therefore, the lignin-based chemically cross-linked polyvinyl alcohol composite film of the present invention has excellent moisture resistance relative to polyvinyl alcohol film, and the prepared lignin-based chemically cross-linked polyvinyl alcohol composite film has high elongation at break and high resilience in a high humidity environment.

[0033] In the present invention, the mass fraction of the lignin is 30-50% of the total mass of the lignin, succinic anhydride and polyvinyl alcohol. The content of lignin will affect the mechanical properties. When the content of lignin is too little, the cross-linked network is not dense enough, so the moisture resistance and resilience are poor; when the content of lignin is too much, too many nucleation sites will be formed. Due to the three-dimensional structure of lignin itself, the distance between polyvinyl alcohol molecules is too large, so the fracture stress declines seriously.

[0034] In the present invention, the mass ratio of succinic anhydride to polyvinyl alcohol is 1:(0.8-1.2). Succinic anhydride is used as a cross-linking agent in a relatively large amount (accounting for about 30-40wt% of the total mass of lignin, succinic anhydride and polyvinyl alcohol), which can facilitate its full reaction with hydroxyl groups. In addition, succinic anhydride has low cost, wide sources and good degradability.

[0035] In the present invention, the total mass of lignin, succinic anhydride and polyvinyl alcohol and the amount of solvent used are 1g: (2.5-5)mL. The appropriate amount of solvent can ensure that the solute is fully dissolved to make the modification more uniform, thereby facilitating the uniform performance of the prepared membrane; and can also avoid waste caused by excessive solvent.

[0036] In the present invention, the solvent is selected from one or more of dimethyl sulfoxide, N,N-dimethylformamide or N,N-dimethylacetamide. The solvent should have good solubility for lignin, polyvinyl alcohol, succinic anhydride and catalyst to ensure sufficient cross-linking.

[0037] In the present invention, the catalyst is selected from N,N-dimethylbenzylamine, acetone or 1-methylimidazole, preferably N,N-dimethylbenzylamine. The mass fraction of the catalyst is 15-25% of the mass of succinic anhydride. When the catalyst is N,N-dimethylbenzylamine, it has good Lewis base properties, provides a large amount of electron clouds for the reaction, and interacts with the carbonyl oxygen in the carboxylic acid. This interaction can enhance the electropositivity of the carbonyl carbon, making it easier to be attacked by alcohols, thereby accelerating the esterification reaction.

[0038] In the step of obtaining the succinic anhydride esterified lignin solution by reaction in the presence of a catalyst according to the present invention, the reaction temperature is 55 to 70° C., more preferably 58 to 65° C., and the reaction time is 5 to 10 hours.

[0039] In the step of drying and film formation after the reaction of the present invention, the reaction temperature is 55 to 70° C., more preferably 58 to 65° C., and the reaction time is 5 to 10 hours.

[0040] In the step of drying and forming a film after the reaction of the present invention, the drying is vacuum drying, the drying temperature is 55 to 70° C., and the drying time is 8 to 24 hours.

[0041] The reaction process of the present invention is carried out under stirring conditions. The present invention does not impose any special restrictions on the stirring conditions, and the stirring conditions commonly used in the art can be adopted.

[0042] The present invention does not impose any special restrictions on the specific steps of drying and film forming, and the film forming method using the solution casting method commonly used in the art can be used.

[0043] The present invention also provides a lignin-based chemically cross-linked polyvinyl alcohol composite film prepared by the above-mentioned preparation method. The lignin-based chemically cross-linked polyvinyl alcohol composite film of the present invention has good mechanical properties, and the elongation at break can be as high as 400% or more under dry conditions, and can still be maintained at more than 200% in a high humidity environment. At the same time, it has good resilience in a high humidity environment, which expands the application field of the lignin-based chemically cross-linked polyvinyl alcohol composite film.

[0044] The technical solution of the present invention is further described below in conjunction with specific embodiments.

[0045] Example 1

[0046] This embodiment provides a chemically cross-linked polyvinyl alcohol film, wherein the mass fraction of lignin is 30% of the total mass of lignin, succinic anhydride and polyvinyl alcohol. The specific preparation method is as follows:

[0047] Weigh 4.29 g of lignin powder, weigh 5 g of succinic anhydride powder, add 50 mL of dimethyl sulfoxide and 1 g of N,N-dimethylbenzylamine, and stir magnetically at 60 ° C for 6 h to obtain a succinic anhydride esterified lignin solution. Weigh 5 g of polyvinyl alcohol powder, add it to the succinic anhydride esterified lignin solution, stir magnetically at 60 ° C for 6 h to obtain a solution after cross-linking reaction. Transfer the solution after cross-linking reaction to a polystyrene petri dish, dry it in a vacuum drying oven at 60 ° C for 12 h, and cool it to room temperature to obtain a lignin-based chemically cross-linked polyvinyl alcohol composite film.

[0048] Example 2

[0049] This embodiment provides a lignin-based chemically cross-linked polyvinyl alcohol composite film, wherein the mass fraction of lignin is 40% of the total mass of lignin, succinic anhydride and polyvinyl alcohol. The specific preparation method is as follows:

[0050] Weigh 6.67 g of lignin powder, weigh 5 g of succinic anhydride powder, add 50 mL of dimethyl sulfoxide and 1 g of N,N-dimethylbenzylamine, and stir magnetically at 60 ° C for 6 h to obtain a succinic anhydride esterified lignin solution. Weigh 5 g of polyvinyl alcohol powder, add it to the succinic anhydride esterified lignin solution, stir magnetically at 60 ° C for 6 h to obtain a solution after cross-linking reaction. Transfer the solution after cross-linking reaction to a polystyrene petri dish, dry it in a vacuum drying oven at 60 ° C for 12 h, and cool it to room temperature to obtain a lignin-based chemically cross-linked polyvinyl alcohol composite film.

[0051] Example 3

[0052] This embodiment provides a lignin-based chemically cross-linked polyvinyl alcohol composite film, wherein the mass fraction of lignin is 50% of the total mass of lignin, succinic anhydride and polyvinyl alcohol. The specific preparation method is as follows:

[0053] Weigh 10g of lignin powder, weigh 5g of succinic anhydride powder, add 50mL of dimethyl sulfoxide and 1g of N,N-dimethylbenzylamine, and stir magnetically at 60°C for 6h to obtain a succinic anhydride esterified lignin solution. Weigh 5g of polyvinyl alcohol powder, add it to the succinic anhydride esterified lignin solution, stir magnetically at 60°C for 6h to obtain a cross-linked solution. Transfer the cross-linked solution to a polystyrene petri dish, dry it in a vacuum oven at 60°C for 12h, and cool it to room temperature to obtain a lignin-based chemically cross-linked polyvinyl alcohol composite film.

[0054] Comparative Example 1

[0055] The difference between this comparative example and Example 1 is that the mass fraction of lignin in this comparative example is 10% of the total mass of lignin, succinic anhydride and polyvinyl alcohol. The specific preparation method is as follows:

[0056] Weigh 1.11 g of lignin powder, weigh 5 g of succinic anhydride powder, add 50 mL of dimethyl sulfoxide and 1 g of N,N-dimethylbenzylamine, and stir magnetically at 60 ° C for 6 h to obtain a succinic anhydride esterified lignin solution. Weigh 5 g of polyvinyl alcohol powder, add it to the succinic anhydride esterified lignin solution, stir magnetically at 60 ° C for 6 h to obtain a cross-linked solution. Transfer the cross-linked solution to a polystyrene petri dish, dry it in a vacuum drying oven at 60 ° C for 12 h, and cool it to room temperature to obtain a lignin-based chemically cross-linked polyvinyl alcohol composite film.

[0057] Comparative Example 2

[0058] The difference between this comparative example and Example 1 is that the mass fraction of lignin in this comparative example is 20% of the total mass of lignin, succinic anhydride and polyvinyl alcohol. The specific preparation method is as follows:

[0059] Weigh 2.5 g of lignin powder, weigh 5 g of succinic anhydride powder, add 50 mL of dimethyl sulfoxide and 1 g of N,N-dimethylbenzylamine, and stir magnetically at 60 ° C for 6 h to obtain a succinic anhydride esterified lignin solution. Weigh 5 g of polyvinyl alcohol powder, add it to the succinic anhydride esterified lignin solution, stir magnetically at 60 ° C for 6 h to obtain a solution after cross-linking reaction. Transfer the solution after cross-linking reaction to a polystyrene petri dish, dry it in a vacuum drying oven at 60 ° C for 12 h, and cool it to room temperature to obtain a lignin-based chemically cross-linked polyvinyl alcohol composite film.

[0060] Comparative Example 3

[0061] This comparative example provides a method for preparing a polyvinyl alcohol film, and the specific steps are as follows:

[0062] Weigh 5 g of polyvinyl alcohol powder, add it to 50 mL of dimethyl sulfoxide, and stir it magnetically at 60° C. for 12 h. Then transfer the obtained polyvinyl alcohol solution to a polystyrene petri dish, dry it in a vacuum drying oven at 60° C. for 12 h, and then cool it to room temperature to obtain a polyvinyl alcohol film.

[0063] Test example

[0064] 1. Mechanical properties determination:

[0065] The tensile test in dry state and the tensile test exposed to 90% air humidity (90% RH) for 72 hours were performed on the lignin-based chemically cross-linked polyvinyl alcohol films of Examples 1 to 3, Comparative Examples 1 to 2, and the polyvinyl alcohol film of Comparative Example 3 using a texture analyzer at ambient temperature. The composite film was made into a dumbbell-shaped sample (length = 20 mm, width = 4 mm, thickness = 0.1 mm) and used for the tensile test at a speed of 60 mm / min. The test results are shown in Table 1.

[0066] Table 1 Film tensile test data in dry state and high humidity state

[0067]

[0068] The N / A of Comparative Example 1 and Comparative Example 3 in Table 1 indicates that the material is too curled and cannot be stretched after being treated at 90% RH humidity for 72 hours and cut into dumbbell-shaped samples, and is no longer suitable for film tensile testing. It can be seen from Table 1 that with the increase of lignin addition, the fracture strain of the lignin-based polyvinyl alcohol film gradually increases, reaching 1216% when the lignin addition is 50%, and the fracture stress shows a trend of first increasing and then decreasing with the addition of lignin content. After being treated at 90% RH humidity for 72 hours, the fracture stress of all embodiment samples is significantly improved, among which the fracture strain of the sample of Example 1 (lignin addition of 30%) decreases the least and the fracture stress increases the most; when the lignin addition is more than 20%, the composite film can still maintain a good film morphology (meeting the tensile test conditions) under high humidity environment treatment; when the lignin addition is more than 30%, the elongation at break in a high humidity environment can be maintained at more than 200%, and it has good mechanical properties.

[0069] 2. Rebound performance test:

[0070] Resilience test in dry state: The lignin-based chemically cross-linked polyvinyl alcohol films of Examples 1 to 3, Comparative Examples 1 to 2, and the polyvinyl alcohol film of Comparative Example 3 were made into rectangular samples (length = 50 mm, width = 10 mm). The dry film rectangular sample was stretched to 3 times the initial length, held for 1 minute, and then released, and the length of the film after release was measured (Note: the polyvinyl alcohol film of Comparative Example 3 could not be stretched to 3 times the initial length, and here only the resilience test was performed by stretching from 40 cm to 70 cm).

[0071] Immersion rebound performance test: The lignin-based chemically cross-linked polyvinyl alcohol films of Examples 1 to 3, Comparative Examples 1 to 2, and the polyvinyl alcohol film of Comparative Example 3 were cut into rectangles (length = 40 or 50 mm, width = 10 mm), placed in a 20 mL glass bottle filled with tap water and fully soaked for 24 hours. After soaking, the length of the film was tested, and then the wet film rectangular sample was stretched to 3 times the initial length, kept for 1 minute and then released, and the length of the film after release was measured.

[0072] The test results of the rebound performance in the dry state and after immersion are shown in Table 2, and the test process pictures are shown in Figure 1 and Figure 2 shown.

[0073] Table 2 Test results of film resilience in dry state and after immersion

[0074]

[0075]

[0076] Note: The calculation formula of the rebound rate in Table 2 is: Rebound rate (%) = (total elongation - irrecoverable elongation) / total elongation × 100%; "N / A" in Table 2 means that the material swells severely after immersion, such as Comparative Example 1 and Comparative Example 2; or the material is completely dissolved after immersion, such as Comparative Example 3, and it is impossible or not suitable to perform the rebound performance test.

[0077] It can be seen from Table 2 that the addition of lignin enables the material to have resilience performance, and the samples with a high amount of lignin added, such as Examples 1 to 3, still maintain their resilience after soaking and even have an improving trend.

[0078] 3. Degradation performance determination:

[0079] The degradation performance was measured using the lignin-based chemically cross-linked polyvinyl alcohol film of Example 3 (lignin content: 50 wt%). The sample was cut into semicircles for easy observation and buried at a depth of about 2 cm in natural soil. The sample was dug out every 4 days to check for morphological changes and taken photos for record.

[0080] like Figure 3As shown, it can be seen that after the first cycle, obvious wrinkles appeared on the sample surface; at the end of the second cycle, the sample showed a shrinkage trend; at the end of the third cycle, the sample of Example 3 showed serious shrinkage. It can be seen that the lignin-based chemically cross-linked polyvinyl alcohol film of Example 3 became brittle and wrinkled after landfill treatment, which is consistent with the characteristics of the degradation process. It can be seen that even if the lignin content reaches 50%, the lignin-based chemically cross-linked polyvinyl alcohol film still has good degradation performance.

[0081] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a lignin-based chemically cross-linked polyvinyl alcohol composite film, characterized in that: The steps include: Dissolving lignin and succinic anhydride in a solvent, and reacting in the presence of a catalyst to obtain a succinic anhydride esterified lignin solution; Polyvinyl alcohol is added into the succinic anhydride esterified lignin solution, and the solution is dried to form a film after the reaction.

2. The preparation method according to claim 1, characterized in that The mass fraction of the lignin is 30-50% of the total mass of the lignin, succinic anhydride and polyvinyl alcohol.

3. The preparation method according to claim 2, characterized in that: The mass ratio of succinic anhydride to polyvinyl alcohol is 1:(0.8-1.2).

4. The preparation method according to claim 1, characterized in that: The total mass ratio of lignin, succinic anhydride and polyvinyl alcohol to the solvent is 1 g: (2.5-5) mL.

5. The preparation method according to claim 1, characterized in that: The solvent is selected from one or more of dimethyl sulfoxide, N,N-dimethylformamide or N,N-dimethylacetamide.

6. The preparation method according to claim 1, characterized in that: The catalyst is selected from N,N-dimethylbenzylamine, acetone or 1-methylimidazole; the mass fraction of the catalyst is 15-25% of the mass of succinic anhydride.

7. The preparation method according to claim 1, characterized in that: In the step of obtaining the succinic anhydride esterified lignin solution by reaction in the presence of a catalyst, the reaction temperature is 55 to 70° C. and the reaction time is 5 to 10 hours.

8. The preparation method according to claim 1, characterized in that: In the step of drying and forming a film after the reaction, the reaction temperature is 55 to 70° C. and the reaction time is 5 to 10 hours.

9. The preparation method according to claim 1, characterized in that: In the step of drying and forming a film after the reaction, the drying is vacuum drying, the drying temperature is 55 to 70° C., and the drying time is 8 to 24 hours.

10. The lignin-based chemically cross-linked polyvinyl alcohol composite film prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Silicon-containing waterborne UV bio-based unsaturated polyester and preparation method thereof

    CN109749071A

  • Method for preparing lignin anhydride cured epoxy resin by one-pot process

    CN110358055A

  • Anionized lignocellulose nanofibril as well as preparation method and application thereof

    CN115368585A

  • Preparation method of demethylated lignin modified polyvinyl alcohol-based degradable plastic

    CN118063911A

  • Meltable lignin compositions, method for producing them and their uses

    US20210040273A1